2019
DOI: 10.1111/tct.13069
|View full text |Cite
|
Sign up to set email alerts
|

Soliciting feedback on the wards: a peer‐to‐peer workshop

Abstract: Background: For medical students, soliciting feedback is a critical but difficult skill that merits proper training. This skill may be taught effectively by peers who have experienced challenges with feedback on the wards. Methods: Two medical students developed and taught a workshop on feedback skills. The workshop was presented to 248 third-year students. The workshop trained students in soliciting, receiving and responding to feedback through interactive discussions of case scenarios. Students were given pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Our findings are consistent with previous studies (Bing-You et al 1998;Milan et al 2011;Noble et al 2020;Yau et al 2020) that demonstrate it is possible through educational interventions to change student perceptions of their role in feedback. Further, our study has shown that this can lead to behaviour change (increased feedback-seeking) and improved feedback experience (increased feedback received and increased satisfaction).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings are consistent with previous studies (Bing-You et al 1998;Milan et al 2011;Noble et al 2020;Yau et al 2020) that demonstrate it is possible through educational interventions to change student perceptions of their role in feedback. Further, our study has shown that this can lead to behaviour change (increased feedback-seeking) and improved feedback experience (increased feedback received and increased satisfaction).…”
Section: Discussionsupporting
confidence: 93%
“…Following the workshop, we demonstrated a marked improvement in the frequency of feedback-seeking by students, accompanied by increased receipt of feedback and increased satisfaction with feedback. Increased student intention to seek feedback has been reported following education (Yau et al 2020). To our knowledge, only one other study has demonstrated an increase in actual feedback-seeking (Milan et al 2011), however, changes in frequency of, and satisfaction with, feedback received were not measured in that study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,9,10 Previously published studies describing workshops targeted to the feedback recipient have reported subjective measures of improvement, including increased confidence and frequency in feedback-seeking behaviors, but did not include any objective measures of performance in demonstrating how to effectively receive feedback. [11][12][13][14][15] While the majority of the current published literature primarily has focused on faculty development of the feedback provider in delivering feedback, [16][17][18] we directed our attention to the learner (feedback recipient). Our workshop addressed simple strategies for effectively receiving feedback, targeted to medical students just prior to the start of their first clinical clerkship.…”
Section: Introductionmentioning
confidence: 99%